Developing Video Based Language Learning to Support Students’ Autonomous Study in Higher Education Setting - Sitti Rahmawati; Muliadi Muliadi (Pascasarjana Universitas Negeri Makassar, 2022)
The pilot study focuses on three issues: how to articulate the need for learning videos in the language course, how to design learning videos in the language course, and how to articulate the feasibility and practicality of learning videos in the language course at the Faculty of Letters, Muslim University of Indonesia. This study employs a qualitative descriptive approach. The findings of this study indicated that students required more engaging learning resources than books and presentation slides, one of which is a learning video packaged in animation to capture students' attention and motivate them to learn the content or material in the learning video. Language learning videos with material paragraphs are produced using the video animation concept, specifically whiteboard animation. This design was picked based on the animated video's attractiveness to the audience in order to pique their interest in the material or film after it is shown. The viability of learning videos as determined by validation results from media and material experts on newly designed Indonesian language learning films is extremely good. The video's form or presentation, as well as the content included inside, are adequate and sufficient to allow it to forward to the following stage, namely testing to ascertain the answers or replies of lecturers and students. The practicality of the learning videos, as determined by lecturers and students' reactions, is extremely good; there are no substantial barriers to lecturers and students using these learning videos.